RIAU SONGKET: ESTABLISHING HARMONY WITH THE ENVIRONMENT USING LOCAL WISDOM VALUES - Suroyo, Suroyo; Entas, Derinta; Putra, Bima Maulana; Sorente, Antonia (Balai Penelitian dan Pengembangan Agama Makassar, 2024)
Songket Riau is a traditional fabric that is synonymous with the culture of the people in Riau, Indonesia. However, the practice of making this fabric has been affected by environmental damage caused by human activities. This research aims to explore the values of local wisdom in preserving the environment through the production of Songket Riau. The study used a qualitative critical discourse analysis approach and was conducted in Bandar Senapelan, the main production area of Songket Riau. Primary and secondary data were collected, and data analysis was conducted using in-depth interviews and content analysis. The results show that the production of Songket Riau can be done in harmony with the environment by implementing practices such as using natural dyes, reducing waste, and respecting the environment. This study concludes by recommending that the government and stakeholders should promote the use of local wisdom in preserving the environment in the production of Songket Riau. This will ensure the sustainability of the cultural heritage and the environment.